The impact of remote work in crisis management on the outbreak of the Coronavirus (Covid-19) - An exploratory study on the staff of King Abdulaziz University in Jeddah Governorate - - Samaraddin, Rasha Rashad (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to identify the impact of remote work in crisis management when an outbreak of the new Corona virus (Covid-19) from the viewpoint of employees (male and female) of King Abdulaziz University. The researcher used the descriptive approach and the questionnaire as a tool to collect data from a simple random sample consisting of (30) employees (male and female). The data were processed statistically, and the study showed several results, the most important of which are: There is an effect of remote work as a whole in crisis management at the outbreak of the Corona virus emergence (Covid-19) from the viewpoint of employees of King Abdulaziz University, and also the employees of King Abdulaziz University see that there is an impact of the dimension of "information technology" in the management Crises at the new CoronaVirus outbreak (Covid-19),ࢫwhile there is no effect on the two dimensions of “communication and skills” in crisis management at the outbreak of virus corona(Covid-19). There is also an effect of age on crisis management at the outbreak of the new Corona virus (Covid-19) from the viewpoint of male and female employees of King Abdulaziz University. There is no effect of gender, educational qualification, years of experience, and type of jo b in crisis management at the outbreak of the new CoronaVirus (Covid-19) is seen from the viewpoint of male and female employees of King Abdulaziz University. The study recommends the importance of working to provide communication channels for employees to enable them to perform their work in a safe manner, and to work on using software that contributes to reducing error during remote work, and to conduct training courses and workshops for King Abdulaziz University employees to train them in problem-solving skills while working remotely. And the use of experts and specialists from outside the university - if necessary - to prepare plans to restore its activity.
Keywords: remote work; crisis management; novel coronavirus (Covid-19); King Abdulaziz University